The Effect of Particle Size and Solvent Type On The Gallic Acid Yield Obtained from Labisia Pumila by Ultrasonic Extraction - Afiqah, Yeop; Jessinta, Sandanasam; Sook, Fun Pan; Sureena, Abdullah; M. M., Yusoff; Jolius, Gimbun (EDP Sciences, 2017)
This paper presents the effect of particle size and solvent type on the gallic acid (GA) extraction yield obtained from Labisia pumila. The GA extraction from a grinded dried plant material (66.66 μm to 1055.18 μm) was performed using the sonicator probe. The GA quantification and identification was performed using a liquid chromatography with photodiode array detector. Exact match between the spectra obtained from the plant extract and external standard was found indicating a presence of GA. In addition, matching of residence time between the standard and plant extract are also observed. It was found that particle size significantly affects the yield of GA and the highest yield (0.150 mg GA/g DW) was obtained using the particle size around 125 μm. Solvent type does also plays an important role in GA extraction. The result shows that extraction using water as solvent yielded about 29% higher GA content (0.126 mg GA/g DW) than that of 10% ethanol (0.098 mg GA/g DW). The findings in this work may serve as a useful guide to select the particle size and solvent used to maximise GA extraction from L. pumila.